Comparison of thiopentone with lidocaine spray vs propofol for laryngeal mask airway insertion at tikur anbessa specialized hospital. A prospective cohort study. (June 2021) - Belete, Engidawork; W/Yahones, Misrak; Aweke, Zemedu; Dendir, Getahun; Mola, Simeneh; Neme, Derartu; Melaku, Getnet; Ahmed, Siraj; Regasa, Teshome; Tesfaye, Brook
Abstract: Background: Insertion of laryngeal mask airway (LMA) requires an adequate depth of anesthesia. Optimal insertion conditions and hemodynamic stability during LMA insertion are mainly influenced by the choice of the intravenous induction agent. Propofol was recommended as a standard induction agent for LMA insertion. Due to unavailability and cost for treatment Propofol is not easily availed, thus this study aimed at assessing the effect of thiopentone with lidocaine spray compared to Propofol on hemodynamic change and LMA insertion on the patient undergoing elective surgery. Methods: Eighty-four participants were followed in a prospective cohort study based on the induction type of either thiopentone-lidocaine group (TL) or Propofol (P). Hemodynamic variables, LMA insertion condition, apneic time, and cost of treatment during the perioperative time were recorded. Data were checked for normality using the Shapiro-Wilk test. Numeric data were analyzed unpaired student's t-test or Manny Whitney test. Categorical data were analyzed by the chi-square test. A p-value ≤ 0.05 was considered a statistically significant difference. Result: The comparison of data showed that a significant reduction in mean arterial blood pressure (MAP) in the Propofol group during the first 10 min. The MAP at first minute after LMA insertion was 78.4 ± 5.5 in the Propofol group compared to 81.8 ± 5.6 in thiopentone-lidocaine group p < 0.001. the mean MAP at 5th and 10th minutes after LMA insertion is also significantly lower in the Propofol group compared to the thiopentone-lidocaine group, p < 0.05. There were no statistically significant differences regarding the heart rate change and insertion conditions between the two groups. Mean apneic time was 138 ± 45.8 s in the Propofol group and 85 ± 13.8 s in thiopentone-lidocaine group p < 0.001. Thiopentone-lidocaine group had a lower treatment cost compared to the Propofol group. Conclusion: Thiopentone with 10% topical Lignocaine is an alternative for the insertion of LMA to Propofol, with better hemodynamic stability and cost-effectiveness. Highlights: Insertion of laryngeal mask airway requires an adequate depth of anesthesia. The choice of induction agent influence the optimal insertion conditions of LMA. The hemodynamic stability can also be affected by types of induction agent. Thiopentone with 10% topical Lignocaine is an alternative for the insertion of LMA.